Cardiac damage and tropism of severe acute respiratory syndrome coronavirus 2 - Tangos, Melina; Jarkas, Muhammad; Akın, Ibrahim; El-Battrawy, Ibrahim; Hamdani, Nazha (Current opinion in microbiology, 2024)
Until now, the World Health Organization registered over 771 million cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection worldwide, of which 6.97 million resulted in death. Virus-related cardiovascular events and pre-existing heart problems have been identified as major contributing factors to global infection-related morbidity and mortality, emphasizing the necessity for risk assessment and future prevention. In this review, we highlight cardiac manifestations that might arise from an infection with SARS-CoV-2 and provide an overview of known comorbidities that worsen the outcome. Additionally, we aim to summarize the therapeutic strategies proposed to reverse virus-associated myocardial damage, which will be further highlighted in this review, with an outlook to successful recovery and prevention.